Leptospira spp. and Rickettsia spp. as pathogens with zoonotic potential causing acute undifferentiated febrile illness in a central-eastern region of Peru - Silva-Caso, Wilmer (2024)
Objetive: this study was to determine the relationship between acute febrile illness and bacterial pathogens with zoonotic potential that cause emerging and re-emerging diseases in a central-eastern region of Peru. Results: Out of the 279 samples analyzed, 23 (8.2%) tested positive for infection by Rickettsia spp., while a total of 15 (5.4%) tested positive for Leptospira spp. Women had a higher frequency of infection by Rickettsia spp., with 13 cases (53.3%), while men had a higher frequency of infection by Leptospira spp., with 10 cases (66.7%). The most frequently reported general symptom was headache, with 100.0% (n = 23) of patients with Rickettsia (+) and 86.7% (n = 13) of patients with Leptospira (+) experiencing it. Arthralgia was the second most frequent symptom, reported by 95.6% (n = 22) and 60% (n = 9) of patients with Rickettsia (+) and Leptospira (+), respectively. Myalgia was reported by 91.3% (n = 21) and 66.7% (n = 10) of patients with Rickettsia (+) and Leptospira (+), respectively. Retroocular pain, low back pain, and skin rash were also present, but less frequently. Among the positives, no manifestation of bleeding was recorded, although only one positive case for Leptospira spp. presented a decrease in the number of platelets.